Parking space indicator - Hu, Kenny Pon Nuon (Universiti Malaysia Sarawak, (UNIMAS), 2001)
Nowadays, the amount of land transport vehicle in our country has increased drastically from year to year. Consequently, one of the most important characteristic in new develop buildings such as shopping complex and condominium are equipped with parking spaces in their design. The main objective of this project is to optimize the management of parking space. ln order to achieve this objective, it is important to design a circuit, which it. capable of detecting the occurrence of free parking space. By using this method, the system acknowledges the users or drivers about the parking space available in certain area or compound. Hence, it would definitely help the users to save their time, energy and money. Therefore, the intent of this thesis is to describe an overview of combination between optoelectronic circuit and programmable logic control {PLC) which implement this project successfully.